Using realist evaluation to assess primary healthcare teams' responses to intimate partner violence in Spain - Isabel Goicolea; Anna-Karin Hurtig; Miguel San Sebastian; Bruno Marchal; Carmen Vives-Cases (Elsevier, 2015)
Objective: Few evaluations have assessed the factors triggering an adequate health care response to intimate partner violence. This article aimed to: 1) describe a realist evaluation carried out in Spain to ascertain why, how and under what circumstances primary health care teams respond to intimate partner violence, and 2) discuss the strengths and challenges of its application. Methods: We carried out a series of case studies in four steps. First, we developed an initial programme theory (PT1), based on interviews with managers. Second, we refined PT1 into PT2 by testing it in a primary healthcare team that was actively responding to violence. Third, we tested the refined PT2 by incorporating three other cases located in the same region. Qualitative and quantitative data were collected and thick descriptions were produced and analysed using a retroduction approach. Fourth, we analysed a total of 15 cases, and identified combinations of contextual factors and mechanisms that triggered an adequate response to violence by using qualitative comparative analysis. Results: There were several key mechanisms -the teams' self-efficacy, perceived preparation, women-centred care-, and contextual factors -an enabling team environment and managerial style, the presence of motivated professionals, the use of the protocol and accumulated experience in primary health care- that should be considered to develop adequate primary health-care responses to violence. Conclusion: The full application of this realist evaluation was demanding, but also well suited to explore a complex intervention reflecting the situation in natural settings.